An Analysis of the Effect of Financial Planning on the Financial Resilience of Teachers Who Use Online Loans - Fatikha, Khusnul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the impact of financial planning on financial resilience among teachers who use online loans. The methodology used is Moderated Regression Analysis (MRA) conducted on 109 teachers in Surabaya and Sidoarjo using Google Forms questionnaire. The results show a significant positive impact of financial planning on financial resilience. teachers who are actively involved in financial planning manage their income and expenses better and are better prepared for financial shocks.